Opportunities and Challenges for Developing Thematic Villages for the Independence of Malang City - Iswari, Hanif Rani; Indriani, Tantri (Badan Perencanaan Pembangunan Kota Malang, 2024)
This research reviews the phenomenon of thematic village development in Malang City as an innovative solution to increase the city's independence and sustainability. The aim of the research is to identify opportunities and challenges related to the development of thematic villages and explore their impact on the tourism sector, local economy and community quality of life. The method used is descriptive qualitative with a SWOT analysis approach, which allows identifying strengths, weaknesses, opportunities and threats related to the development of thematic villages. The research results show that thematic villages have significant potential for further growth and development, but are also faced with challenges such as limited infrastructure and threats such as competition and policy changes. The proposed development strategy includes infrastructure improvements, more aggressive promotion, training for local communities, and risk mitigation efforts. With a holistic approach and support from various related parties, the development of thematic villages in Malang City can make a positive contribution to local tourism and the economy of the local community.